Comparison of treatment to improve gastrointestinal functions after colorectal surgery within enhanced recovery programmes: a systematic review and meta-analysis - Jean F. Hamel (Nature Portfolio, 2021)
Abstract Despite a significant improvement with enhanced recovery programmes (ERP), gastro-intestinal (GI) functions that are impaired after colorectal resection and postoperative ileus (POI) remain a significant issue. In the literature, there is little evidence of the distinction between the treatment assessed within or outside ERP. The purpose was to evaluate the efficiency of treatments to reduce POI and improve GI function recovery within ERP. A search was performed in PubMed and Scopus on 20 September 2019. The studies were included if they compared the effect of the administration of a treatment aiming to treat or prevent POI or improve the early functional outcomes of colorectal surgery within an ERP. The main outcome measures were the occurrence of postoperative ileus, time to first flatus and time to first bowel movement. Treatments that were assessed at least three times were included in a meta-analysis. Among the analysed studies, 28 met the eligibility criteria. Six of them focused on chewing-gum and were only randomized controlled trials (RCT) and 8 of them focused on Alvimopan but none of them were RCT. The other measures were assessed in less than 3 studies over RCTs (n = 11) or retrospective studies (n = 2). In the meta-analysis, chewing gum had no significant effect on the endpoints and Alvimopan allowed a significant reduction of the occurrence of POI. Chewing-gum was not effective on GI function recovery in ERP but Alvimopan and the other measures were not sufficiently studies to draw conclusion. Randomised controlled trials are needed. Systematic review registration number CRD42020167339.